2017
DOI: 10.1021/acs.est.7b03952
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Susceptibility of Functional Groups of Poly(ether sulfone)/Polyvinylpyrrolidone Membranes to NaOCl: A Two-Dimensional Correlation Spectroscopic Study

Abstract: A clear understanding of membrane aging process is essential for the optimization of chemical cleaning in membrane-based facilities. In this study, two-dimensional (2D) Fourier transformation infrared (FTIR) correlation spectroscopy (CoS) analysis was first used to decipher the sequential order of functional group changes of NaOCl-aged poly(ether sulfone)/polyvinylpyrrolidone (PES/PVP) membranes. The synchronous maps showed 12 major autopeaks in total. Based on the asynchronous maps, a similar aging sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 54 publications
5
25
1
Order By: Relevance
“…For pristine membrane, apart from several characteristic peaks of PES (i.e., 1580, 1486, 1320, 1292, 1241, 1150, 1105 cm −1 ) exhibiting high absorption intensity, an obvious band at 1668 cm −1 was observed. The band at 1668 cm −1 represents the stretching vibration of the amide unit in PVP, and its intensity has been extensively used as an indicator of the content of PVP [16,34,35,36,37]. Similar to previous studies, NaClO aging caused decrease of intensity of the peak at 1668 cm −1 due to PVP oxidation /dislodgement, and new peaks at 1700 and 1772 cm −1 representing oxidation products of PVP were observed.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…For pristine membrane, apart from several characteristic peaks of PES (i.e., 1580, 1486, 1320, 1292, 1241, 1150, 1105 cm −1 ) exhibiting high absorption intensity, an obvious band at 1668 cm −1 was observed. The band at 1668 cm −1 represents the stretching vibration of the amide unit in PVP, and its intensity has been extensively used as an indicator of the content of PVP [16,34,35,36,37]. Similar to previous studies, NaClO aging caused decrease of intensity of the peak at 1668 cm −1 due to PVP oxidation /dislodgement, and new peaks at 1700 and 1772 cm −1 representing oxidation products of PVP were observed.…”
Section: Resultssupporting
confidence: 70%
“…However, permeability of membranes aged by NaClO at pH 9 and 11 were increased to 5.75 and 3.84 times of that of the pristine membrane, respectively. Although the extent of increase varied depending on exposure dose and aging conditions, permeability increase of PES membrane due to NaClO aging has been reported in many studies [13,16,17,32,33,34], and it was commonly attributed to the increase of pore size and porosity [11]. The similar permeability of pristine, control, and H 2 O 2 -aged membranes suggested that pore structure of the PES membrane was not altered obviously by alkaline or H 2 O 2 under the aging conditions in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be seen that there was no obvious difference between the PVP and nanofiber network be- cause the embedding content of NPLs was very low. There were a number of absorption characteristics of PVP observed in the FTIIR curves, the bond at 1663 cm −1 is assigned to the C− −O vibration of the amide groups, and the bond located at 1439 cm −1 and 1391 cm −1 were assigned with the cyclic C−H structures of pyrrolidine in PVP [32]. Moreover, the peaks at 2982 cm −1 and 2875 cm −1 were related to the stretching vibration of C−H and the broad band from 3583 cm −1 to 3081 cm −1 related to the overlap of the stretching vibrations of O−H group with N−H group [33].…”
Section: Resultsmentioning
confidence: 99%